2022
DOI: 10.5935/0004-2749.20220066
|View full text |Cite
|
Sign up to set email alerts
|

Structural alterations of the choroid evaluated using enhanced depth imaging optical coherence tomography in patients with coronavirus disease

Abstract: To assess choroidal changes using enhanced depth imaging optical coherence tomography in coronavirus disease . Methods: Thirty-two patients with moderate COVID-19 and 34 healthy subjects were included in the study. Choroidal thickness was measured at 3 points as follows: at the subfovea, 1500 mm nasal to the fovea, and 1500 mm temporal to the fovea. The total choroidal area, luminal area, stromal area, and choroidal vascular index were measured with Image-J. All the measurements were performed during the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…They stated that these results were associated with vascular damage, hypercoagulability, and hyperinflammation factors causing ischemia in the choriocapillaris, leading to a decrease in CVI. The authors state that the results at four months after remission are close to the measurements of the control group [34] . A study comparing the group with mild COVID-19 patients and the healthy group found that CVI, LA and TCA significantly decreased in the patient group.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…They stated that these results were associated with vascular damage, hypercoagulability, and hyperinflammation factors causing ischemia in the choriocapillaris, leading to a decrease in CVI. The authors state that the results at four months after remission are close to the measurements of the control group [34] . A study comparing the group with mild COVID-19 patients and the healthy group found that CVI, LA and TCA significantly decreased in the patient group.…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, other studies found that the central foveal and choroidal thicknesses decreased in the COVID-19 group, but this decrease did not reach statistical significance [ 33 , 34 ]. On the contrary, Abrishami et al stated that the subfoveal nasal and temporal ChT was measured higher in the active period of the disease [31] .…”
Section: Discussionmentioning
confidence: 70%
“…Others showed a decreased CVI during the COVID-19 disease with a reversible fashion some months after discharge, suggesting reversible and multiple mechanisms (ischemic and inflammatory) of COVID-19 on ocular perfusion [ 17 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent preprint, Kocamis and associates [10] investigated the choroidal alterations in patients with COVID-19 and demonstrated a lower amount of CVI in patients with COVID-19 than healthy control eyes. Despite the apparent difference between the present study results, our results cannot be compared with the mentioned study for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…While the validity of these findings has been questioned by attributing the lesions to the normal retinal vessels [8], later studies also confirmed the retinal microvascular changes [4,9]. In addition to retinal manifestations, choroid can also be involved during the disease course [10,11].…”
Section: Introductionmentioning
confidence: 99%